2013
DOI: 10.2478/jomb-2013-0006
|View full text |Cite
|
Sign up to set email alerts
|

Genotyping of GATA4 Gene Variant (G296S) in Malaysian Congenital Heart Disease Subjects by Real-Time PCR High Resolution Melting Analysis

Abstract: SummaryBackground: Congenital heart disease (CHD) is the most common birth defect; however, the underlying etiology is unrecognized in the majority of cases. GATA-binding protein 4 (GATA4), a cardiac transcription factor gene, has a crucial role in the cardiogenesis process; hence, a number of heterozygote sequence variations were identified as a cause of CHD. G296S heterozygote variant is the most frequently reported GATA4 gene sequence alteration. This study aims to investigate the role of G296S variant of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 35 publications
0
3
0
Order By: Relevance
“…Subsequently, this association was reproduced by Lee ( 23 ) and He ( 24 ) in Korean and Chinese populations, respectively. Overall, the role of rs4673 in AMI is not clear yet and studies with larger sample size are necessary to resolve this controversy ( 25 ).…”
Section: Discussionmentioning
confidence: 99%
“…Subsequently, this association was reproduced by Lee ( 23 ) and He ( 24 ) in Korean and Chinese populations, respectively. Overall, the role of rs4673 in AMI is not clear yet and studies with larger sample size are necessary to resolve this controversy ( 25 ).…”
Section: Discussionmentioning
confidence: 99%
“…A number of previous studies have shown association of the variant rs104894073 (c.886G > A) of exon 3 of GATA4 gene with VSD [ 12 ]. This variant reduces the affinity of the GATA4 transcription factor to bind with DNA causing reduction in its transcriptional activity [ 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…A genetic basis for drug res ponse can be determined using the candidate genes app roach or genome-wide association studies. Pharma co genetics is the study of the effect of variation in a single gene on drug response, including both efficacy and toxicity, with the aim to provide the adequate dosage for each patient with maximum clinical benefit and minimal side (1)(2)(3)(4). Sources of pharmacogenetic variation could be divided into three broad categories: pharmacokinetic (variability in concentration of drug at site of drug effect), pharmacodynamic (variability in drug ability to influence its target) and those related with the underlying disease mechanism (variability in disease being treated).…”
Section: Introductionmentioning
confidence: 99%